Social Support, Trust and Purchase Intention in Social Commerce Era - Makmor, Nurkhalida; Shah Alam, Syed; Abd Aziz, Norzalita (International Journal of Supply Chain Management, 2018)
Due to increasing numbers of purchases in the onlineindustry has created trust as a critical path in an online environment. In fact, it is more critical when trust has identified as crucial in online commerce. Consumers are reluctant to have a purchase intention when they distrust towards the website.  Consumers nowadays, who represent the future buyers, seem to have reasons how they can trust in online commerce and ultimately lead them to have purchase intention. Drawn from social support theory, trust and purchase intention, this research empiricallyis to test which characters of social support (emotional and informational support) have significant influence purchase intention and to test whether the trust has a significant influence on purchase intention.  Furthermore, to test the mediating effects oftrust in social commerce.  The research conducted in the quantitativeapproach and used non-probability (convenience sampling) by using questionnaire surveys. A correlation and multiple regression analyses were applied. A total of 200 respondents participated. Our results shed some lights on social commerce literature. The result confirms that there is a relationship between social supports such as emotional and informational support on purchase intention. Finding also revealed that trust as fully mediates the relationship between the variables. This research can entirelycontribute to the literature by providing and introducing to both marketers and consumers by identifying the factors influencing purchase intention in social commerce.